An Integrability Condition for Monge-Ampere Equations on a Kahler Manifold (Journal of Partial Differential Equations, 1998)
The symmetry group of the Monge-Ampère equation on a Kähler manifold is determined and an integrability condition on the solution is derived as a conservation law.
Keywords: Complex Mongc-Ampère equntion; Futaki's obstruction; Lie symmetry group; Noether's theorem and conservation laws